Training of Community health workers for mental health care in primary care - empowering people to take care of peaple - Munari, Denize Bouttelet; Melo, Terezinha Silvério de; Oliveira, Marina Barbosa de; Barbosa, Camila Cândida; Queiroz, Ana Carolina de Castro Mendonça; Araújo, Bruna França Martins de (Tempus – Actas de Saúde Coletiva, 2011)
Public health practice in Brazil calls for an ongoing search for qualified health providers for implementation of the Brazilian National Health System (SUS). In this context, mental health care is a major challenge due to its particularities. It requires establishing a channel of communication between its specific attributes and the Family Health Strategy for bringing together the community and specialized outpatient care. The objective of the present study was to report the experience of a training workshop on mental health for community health agents (CHA) organized by faculty and graduate students in nursing at Universidade Federal e Católica de Goiás School of Nursing, State of Goiás, Brazil. This initiative was developed due to a demand by CHA who reported lack of knowledge to meet the needs identified in families and their own mental health needs. The workshop was held biweekly in the second half of 2008 applying the Laboratory Education model, which enables the integration of theory and experiences based on the focus of interest of the subjects. The program was based on the needs of the group then worked through the experiential learning cycle, a key element of this approach. We conclude that involvement, attendance, interest and application of knowledge by CHA proved the efficacy of this model as a strategy capable of developing them as people and professionals.